Exploitation of national or local workers and the liability of the employer - Ali Mohamed, Ashgar Ali (s.n, 2012)
Labour is not and should not be treated as a commodity i.e., workers are not a disposable commodities who can be tossed aside and replaced with ease. All forms of exploitation of workers and abusive practices against workers in the workplace are prohibited by both the international and national instruments. The employment relationship is based on the mutual trust and confidence. The employer ought to be reasonable, honest and forthright with their employees. They should refrain from engaging in conduct that is unfair or is bad faith by being, for example, untruthful, misleading or unduly insensitive. The wrongful conduct of the employer entitles the worker to claim that the employer had evinced an intention no longer to be bound by the contract of employment thus, enabling the worker to regard himself as being dismissed and walk out of his employment. Constructive dismissal signifies that an employer had breached a significant or fundamental term of the contract of employment, express or implied, going to the heart or root of the contract for example, unilaterally varying or reducing the salary of the worker, demotion and withdrawal of fixed travelling and entertainment allowance, among others.